(untitled) (UNED Research Journal, 2026)
Introduction: The Flipped Learning approach reconfigures traditional teaching by moving direct instruction outside the classroom, fostering students’ active engagement and autonomy. Objective: To determine the relationship between the Flipped Learning methodology and English language learning in students of initial teacher training in Secondary Education. Methods: We conducted a correlational study with 50 students from the VI, VIII, and X cycles (2025-II). We applied two Likert-type questionnaires validated by expert judgment (Cronbach’s alpha: 0,987 and 0,985). Results: Most students (71%) reported high flipped learning implementation, which correlated with a high level of English proficiency (72%; rho = 0.800; p = 0.025). Conclusions: The Flipped Learning methodology correlated with good English language learning. We recommend strengthening teacher training in active methodologies to maximize the impact on linguistic production and academic performance.